Managerial performance: The challenge of the future - P. H. Van Den Berg; G. P.J. Pelser (South African Journal of Business Management, 1986)
Measuring the performance of individual managers is difficult in practice because quantitative yardsticks often measure the performance of groups under the control of a manager or the performance of groups spread over departmental boundaries. If managers are measured individually there is a tendency to emphasize quantitative yardsticks only. An effort is also made to measure individual manager's performance by quantifying qualitative yardsticks. The yardsticks that cannot be quantified, that is the innovative aspects of managerial decisions, are thus neglected. The authors propose a model that can be used for the continual improvement of managerial performance. Managerial performance is the degree to which the manager can close the gap between his current and potential performance. The model takes into account that managerial performance consists of both effectiveness and efficiency. The fundamental basis of the model is the creation of continual review sessions that endeavour to improve performance by removal of the causes of substandard performance.
Keywords: 650